Biaya Transaksi, Harga Pokok Produksi Dan Harga Jual Pada Usaha Pembenihan Ikan Patin - Mukhlis Mustofa; Zulkarnain Zulkarnain; Kaizan Kaizan (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2022)
The research objective was to determine the transaction costs and cost of production of catfish hatcheries in the South Metro District, Metro City. The research was conducted in Margorejo Village, Metro Selatan District, Metro City with a total sample of 30 people using the sampling method, namely saturated sampling (census). The results showed that the transaction costs in the catfish hatchery business were information costs of Rp. 14,960.00; coordination fee of IDR 37,635.00; monitoring fee of Rp. 65,700.00 and transportation costs of Rp. 11250.00. The biggest contribution of transaction costs is monitoring fees of 50.72%. While the cost of production and the selling price of the catfish hatchery business in Margorejo Village, Metro Selatan District, Metro City is Rp. 65.61/head and Rp.72.18/head in one cycle.